Move more and sit less pilot intervention for individuals with heart failure. (1st November 2022) - Swartz, Ann M.; Wamsley, Christa; Crownover, Erin; Tarima, Sergey; Gaglianello, Nunzio; Deal, Kristen; Burns, Edith
Abstract: Background: Higher physical activity (PA) and lower sedentary behavior (SB) have been independently associated with lower risk of Heart Failure (HF). However, few individuals with HF engage in sufficient PA to confer benefits and many engage in high amounts of SB. This this feasibility study was conducted to examine changes in steps/day and SB in response to a tailored move more and sit less intervention. Methods: This study used a single group, pre-post study design to assess changes in steps/day, inactive time, and time in moderate- to vigorous-intensity physical activity in individuals with HF stage C and D. Participants completed 1-week baseline assessment and an 11-week intervention. GEE Poisson model was used to evaluate the effect of intervention on change in PA and SB. Results and translational conclusions: Thirteen participants with an average age of 69 ± 13 years that had been living with heart failure for 5.5 ± 4.2 years completed this intervention study. Average steps per day increased significantly over the intervention from 4778 steps/day at baseline to 5518 steps/day post-intervention. Time spent sedentary did not change. Move more and sit less interventions that include behavioral change techniques such as immediate feedback on steps can result in changes in walking behavior. Further strategies for reducing SB in this population should be explored. Highlights: The feasibility of using a smart-phone linked wearable PA device was high. Participants used the tracking devices 99.7% of the time. A telephone-delivered move more, sit less intervention in HF patients resulted in a 16% increase in steps but no change in sedentary behavior. Exploratory analyses suggest time since diagnosis was a positively associated with steps/day. Heart failure patients were more responsive to "move more" recommendations, rather than "sit less" recommendations.